Finding a new policy model for public service broadcasting - Fourie, Pieter J. (Department of Communication Science, University of the Free State, 2005)
The market paradigm in South Africa has eroded public service broadcasting (PSB) values and principles. The adoption of the market paradigm (even in a limited way) has diminished PSB's potential role in development and nation building. In order to secure the future of PSB, a new policy model is needed. In this article such a model is proposed against the background of the need to acknowledge the changed nature of society, democracy, social responsibility, the changed nature of the media and media environment, and the policy paradoxes created by the market paradigm for PSB. Some of the paradoxes related to regulation, funding, access and content are highlighted. The article concludes by stating that the time has come to move beyond PSB as an institution to PSB as a genre spread over the spectrum of the broadcasting industry.
Keywords: Public service broadcasting; Media policy research